A CROSS-GENDERED ANALYSIS OF THE MAIN REFUSAL STRATEGIES AND THEIR REALIZATIONS BY THE IRAQI EFL UNIVERSITY LEARNERS - Zainab Saad Mohammed; Eman Riyadh Adeeb (Universitas PGRI Madiun, 2021)
The current study was set out to scrutinize the EFL Iraqi learners' awareness of the different main strategies of refusal speech acts. Because of the crucial nature of this topic, the researchers tended to base it on gender approach to investigate the substantial differences between the male and female learners in this realm. To this end, a sample of EFL Iraqi university learners was chosen randomly, from the department of English to participate in the questionnaire the researchers built. The data of the study was attained via various suggestive situations the learners exposed to in order to provide their refusal responses. The findings of the analysis reveal that both groups mostly favor to employ the direct refusal strategies more than the indirect and adjuncts to refusal strategies with especial reference to the difference between the two gendered groups due to the unconscious ignorance of the toughness of the face-threatening acts.